Effects on heavy menstrual bleeding and pregnancy of uterine artery embolization (UAE) or myomectomy for women with uterine fibroids wishing to avoid hysterectomy: The FEMME randomized controlled trial. Issue 2 (17th January 2023) - Sirkeci, Fusun; Moss, John; Belli, Anna M.; McPherson, Klim; Daniels, Jane; Manyonda, Isaac; Middleton, Lee; Cheed, Versha; Wu, Olivia; Lumsden, Mary A.; ,
Abstract: Objective: To determine treatment options (myomectomy vs. uterine artery embolization (UAE)) for women wishing to avoid hysterectomy. Methods: A multicenter randomized controlled trial was conducted on 254 women and data were collected on fibroid‐specific quality of life (UFS‐QOL), loss of menstrual blood, and pregnancy. Results: At 4 years, the mean difference in the UFS‐QOL was 5.0 points (95% confidence interval (CI) −1.4 to 11.5; P  = 0.13) in favor of myomectomy. This was not statistically significant as it was at 2 years. There were no differences in bleeding scores, rates of amenorrhea, or heavy bleeding. Of those who were still menstruating, the majority reported regular or fairly regular periods: 36 of 48 (75%) in the UAE group and 30 of 39 (77%) in the myomectomy group. Twelve women after UAE and six women after myomectomy became pregnant (4 years) with seven and five live births, respectively (hazard ratio 0.48, 95% CI 0.18–1.28). There was no difference between the levels of hormones associated with the uterine reserve in each group. Conclusion: Leiomyoma are common in reproductive‐aged women, causing heavy menses and subfertility. Among women with uterine fibroids, myomectomy resulted in better fibroid‐related quality of life at 4 years, compared with UAE but the treatments decreased menstrual bleeding equally. There was also no significant difference in the impact of treatment on ovarian reserve. Synopsis: Women with uterine fibroids were randomized between uterine artery embolization and myomectomy. Quality of life was greater in the myomectomy group at 2 years, but neither menstrual blood loss nor markers of ovarian function differed.